Detection of Leptospira spp. in Animals and Environmental Contaminant by Dark Field Microscopy, Real-time PCR, Microscopic Agglutination Test and Enzyme Linked Immunosorbent Assay - vaidya, Vilas mahadeo; ATUL H NEHETE; RAVINDRA J. ZENDE; RAJASHREE S GANDGE; RAJPAL S KHILLARE (The Indian Journal of Animal Sciences, 2026)
The present investigation is to detect Leptospira spp. in animals and environmental contaminant in and around Mumbai city. A total of 240 samples from buffalo, 190 cattle and 145 dog along with 54 water samples from in and around Mumbai were screened using Dark Field Microscopy (DFM), Real-time polymerase chain reaction (RT-PCR), Microscopic Agglutination Test (MAT) and Enzyme Linked Immunosorbent Assay (ELISA).Altogether 2.50% of tested samples positive by DFM, including four (3.07%) buffalo, one (0.90%) cattle, three (2.06%) dog and three (5.55%) water samples. In cattle, 2 (1.81%) blood samples were found to be positive, whereas urine samples were negative. In buffaloes, 6 (5.38%) blood and 1 (5%) urine samples were found to be positive, whereas in dogs, 7 (5.51%) blood, 1(2%) of urine sample and 8 (14.81%) water samples showed positivity.  MAT analysis of 174 sera revealed 12.26%, 9.09%, and 21.73%, seropositivity in buffalo, cattle and dogs, respectively. 15 (18.75%) of 80 dog sera showed positive results in ELISA. Most prevalent serovars in cattle and buffaloes were Pomona and Tarassovi, while most common serovars were Pyrogenes, Shermani, and Icterohemorrhagiae in dogs. RT-PCR based on the LipL32 gene of Leptospira was successful in quick diagnosis of disease in early stages.  The study indicates that leptospirosis is more prevalent in water in Mumbai due to constant presence of reservoir host which requires multisectoral preventive efforts to minimise the occurrence